Plasma and target-site subcutaneous tissue population pharmacokinetics and dosing simulations of cefazolin in post-trauma critically ill patients. (20th January 2015) - Roberts, Jason A.; Udy, Andrew A.; Jarrett, Paul; Wallis, Steven C.; Hope, William W.; Sharma, Raman; Kirkpatrick, Carl M. J.; Kruger, Peter S.; Roberts, Michael S.; Lipman, Jeffrey
Abstract: Objectives: The objective of this study was to describe the population pharmacokinetics of cefazolin in plasma and the interstitial fluid of subcutaneous tissue of post-trauma critically ill patients and provide clinically relevant dosing recommendations that result in optimal concentrations at the target site. Patients and methods: This was a pharmacokinetic study in a tertiary referral ICU. We recruited 30 post-trauma critically ill adult patients and collected serial total and unbound plasma cefazolin concentrations. Interstitial fluid concentrations were determined using in vivo microdialysis. Population pharmacokinetic analysis and Monte Carlo simulations were undertaken with Pmetrics ® . Fractional target attainment against an MIC distribution for Staphylococcus aureus isolates was calculated. Results: The mean (SD) age, weight, APACHE II score and CLCR were 37.0 (14.1) years, 86.8 (22.7) kg, 16.9 (5.3) and 163 (44) mL/min, respectively. A three-compartment linear population pharmacokinetic model was most appropriate. Covariates included in the model were CLCR on drug clearance and serum albumin concentration and body weight on the volume of the central compartment. The fractional target attainment for a 1 g intravenous 8-hourly dose for a CLCR of 50 mL/min was 88%, whereas for a patient with a CLCR of 215 mL/min, a dose of 2 g 6-hourly achieved 84% fractional target attainment. Conclusions: Clinicians should be mindful of the effects of elevated CLCR and serum albumin concentrations on dosing requirements for post-trauma critically ill patients.